LOPOGRAPHY EXAMINATION WITH PATIENT POST-HARTMANN PROCEDURE AT RADIOLOGY DEPARTMENT RSPAU dr. S. HARDJOLUKITO YOGYAKARTA - Sri Mulyati; Ismi Lulu Walidaeni (Jurnal Imejing Diagnostik (JImeD), 2019)
Backgroud: The research has been done about lopography examination with patient post-Hartmann procedure at radiology department RSPAU dr. S. Hardjolukito Yogyakarta. This research aims to know lopography examination with patient post- Hartmann procedure, giving contrast media and  to know the reason of the use AP and Oblique (RPO and LPO) projection.Methods: The type of this research is qualitative with case study approach. Data were collected by observation, interview, and documentation methods. The subject of this research are radiographers, radiologist, and referring doctor. Data analyse  with Interactive models.Results: The result of the research showed that lopography examination with patient post-Hartmann procedure at radiology department RSPAU dr. S. Hardjolukito Yogyakarta is done with patient preparation diet with low fibrous, a lot of waters  and fasting before examination approximately 10 hours. Giving contrast media to lopography examination with patient post-Hartmann procedure is contrast media water soluble diluted NaCl with ratio 1 : 4 . Total volume is 650 cc. Giving contrast media through anus and stoma.Conclusion: The reason of the use AP and Oblique (RPO and LPO) projection is based of  radiologist advise, based on confirmation with radiologist that projection can maintain the diagnose. AP projection can  show entire colon and Oblique (RPO and LPO) projection can show flexure area.